2019
DOI: 10.3389/fpsyg.2019.02329
|View full text |Cite
|
Sign up to set email alerts
|

Children's Acquisition of Homogeneity in Plural Definite Descriptions

Abstract: Plural definite descriptions give rise to homogeneity effects: the positive The trucks are blue and the negative The trucks aren't blue are both neither true nor false when some of the trucks are blue and some are not, that is, when the group of trucks is not homogeneous with respect to the property of being blue (Löbner, 1987, 2000; Schwarzschild, 1994; Križ, 2015b). The only existing acquisition studies related to the phenomenon have examined children's comprehension only of the affirmative versions of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Previous experimental studies have employed this type of ternary task with children and have shown that they can make use of the middle reward appropriately. In particular, similar to adults, children appear to distinguish between clearly false controls, to which they give the minimal reward, and target items, for which they tend to use the middle value (see Katsos &Bishop 2011 andTieu et al 2017a).…”
Section: Methodsmentioning
confidence: 96%
“…Previous experimental studies have employed this type of ternary task with children and have shown that they can make use of the middle reward appropriately. In particular, similar to adults, children appear to distinguish between clearly false controls, to which they give the minimal reward, and target items, for which they tend to use the middle value (see Katsos &Bishop 2011 andTieu et al 2017a).…”
Section: Methodsmentioning
confidence: 96%
“…Crucially, they do assign the correct interpretation to quantified nominals like "all the things in the bucket", that are rarely used non-maximally in adult languages. Karmiloff-Smith (1981) and Tieu et al (2019) reach a similar conclusion about child French, further suggesting that maximality emerges fairly late in acquisition, reportedly after 6 years of age.…”
Section: Why Are Children Overly Permissive?mentioning
confidence: 74%
“…If this explanation is on the right track, then Pattern 1 may ultimately have the same source as children's well-known difficulty computing certain scalar implicatures until age six or seven, in particular, implicatures derived on the basis of alternatives generated by replacing one word of the assertion (e.g., some in I ate some cookies) by some other lexical material associated with it (e.g., all) (see, e.g., Chierchia et al 2001;Gualmini et al 2001;Noveck 2001). A similar line of reasoning has been used to explain children's failure to enforce maximality in their interpretation of plural definites by Tieu et al (2019). These authors build on Magri's (2014) proposal for deriving maximality effects for plural definites "the N", interpreted as "all the N", as a scalar implicature.…”
Section: Why Are Children Overly Permissive?mentioning
confidence: 95%
“…In recent years, a variety of studies have used a ternary judgment task to investigate implicatures (Katsos & Bishop 2011;Tieu et al 2017a;Renans et al 2018), presuppositions (Abrusan & Szendroi 2013), and homogeneity (Križ & Chemla 2015;Tieu, Kriz & Chemla 2019). As first conceived of in Katsos & Bishop (2011) for implicatures, the idea behind the ternary judgment task is that the lowest valued judgment (e.g., the smallest reward) is reserved for false sentences, the highest valued judgment (e.g., the biggest reward) is reserved for true and felicitous sentences, and the intermediate judgment is meant for true but infelicitous sentences, e.g., sentences with a true literal meaning but a false implicature.…”
Section: Previous Studiesmentioning
confidence: 99%